Methodological Aspects of Training Teachers of Artistic Disciplines in the Context of European Integration Processes - Tkach, Mariia; Fedoryshyn, Vasyl; Hlazunova, Iryna; Mymryk, Mykhailo; Maltseva, Natalia (Harmonia: Journal of Arts Research and Education, 2025)
This research aimed to identify the specific methodological features of training teachers in artistic disciplines, focusing on the specialty 025 “Musical Art” within the context of European integration processes. This study aimed to analyse existing educational and professional programmes, evaluate the quality of specialist training, and examine the incorporation and effectiveness of innovative and interactive technologies in forming the professional competencies of future educators in culture and arts. A qualitative and quantitative analysis was conducted using data from educational programmes at Kyiv National University of Culture and Arts, the National Academy of Managers of Culture and Arts, and Lviv National Academy of Arts. The study included the examination of student surveys, institutional reports, and labour market statistics to assess educational practices, digital technology integration, and alignment with European standards. The impact of external factors such as martial law and the COVID-19 pandemic on the educational process was also considered. The results indicate that while foundational professional competencies and general skills are developed effectively, there is insufficient integration of innovative technologies, “soft” skills, and interdisciplinary approaches. The study revealed challenges in distance learning implementation, resource limitations, and the need for enhanced cooperation with international institutions. The use of virtual and augmented reality and dual education methods remains underutilized. The findings provide a basis for updating educational programmes and methodological support to improve training quality and competitiveness of art discipline educators in the European educational space.